EL SEGUIMIENTO A LA PENSIÓN ALIMENTICIA, A FIN DE GARANTIZAR EL DESARROLLO INTEGRAL DE LOS NIÑOS, NIÑAS Y ADOLESCENTES, EN CUMPLIMIENTO LEGAL Y CONSTITUCIONAL - JIMÉNEZ HIDALGO, NANCY SUSANA (2016)
The present research work I have raised before the need for the law to track maintenance payments received by parents through Social Work for the only beneficiaries are children and adolescents, with the dimension of the problem uncontrollable rates has taken in modern times, now constituting a legal, constitutional and social problem. The problem I have developed under the theme entitled " MONITORING A CHILD SUPPORT ORDER TO ENSURE THE INTEGRAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS IN LEGAL COMPLIANCE AND CONSTITUTIONAL " which has been supported under the doctrinal analysis on the subject has been written, the analysis has allowed me to determine the truth of this problem, which has resulted in that you can make approaches to legal, constitutional and social order, in order to structure a more efficient legal framework to prevent, control and sanction this problem that are outside the law. This has been reflected in the proposed legal reform at the end of this investigation and get to consideration of the National University of Loja, and all those who have some affinity with the material problems of present research